Språk och identitet i Barbro Smeds dramatik - Milekic , Gudrun (Tidskrift för genusvetenskap, 1997)
The characters of the dramatist Barbro Smeds often use a fashion- language or a jargon in their dialogue. By its gaps and contradictions an abyss behind is shown its surface. The speech displays curious sliding motions, and by them the characters pursuit of identity becomes visible. This pursuit contains the "tragic irony" of the characters, as they are searching for their inner most kernel, at the same time as their identity is construed by a perpetual interactive process. The language and the speech make it possible to study this formation of identity, because the individual is construed by the language and is born into an already existing one. The three plays studied are Mars or the Spies of Love, R and Sun and Spring. The first play is an investigation of a couple of upper class jargons, the hospital jargon and the language of the evening courses, the second of the broken Swedish of immigrants and the third of the masculine and patriachal political language. In Mars or the Spies of Love each character has a special version of the jargon and in R an individual version of broken Swedish. In Sun and Spring masculine and feminine language are played out against each other, and by that the sexist structure of the political language is shown. Common to all the plays are the instability of the language and its identity-forming function. Another common trait is the feminist aproach. Mars or the Spies of Love is implicitly feminist, because women are moulded as the stronger ones, those who have the capacity of surviving a changing conception of the universe. In Sun and Spring the feminism is more explicitly expressed by a woman's revenge. Every play has a feminist dramaturgy, e g a couple of lesser peaks instead of one and an associative joining together of scenes rather than a causal. According to Sue-Ellen Case the most important aims of a feminist dramaturgy are deconstruction of the perception of woman in the traditional subject system and putting her into the subjects position. Especially Sun and Spring serves those functions.